The importance of informing about the preventive program for early detection of prostate cancer- a preliminary pilot study - Antonija Lipić; Bojan Miletić; Željko Jovanović (Archives of Gerontology and Geriatrics Plus)
Objectives: The aim was to determine the knowledge of men about prostate cancer and screening methods, and the influence of these factors on participation in prostate cancer screening. Participants and methods: Participants in this observational and cross-sectional study were men aged 40 to 79 years. Participation in the study was voluntary. Data were collected in May 2023 via an anonymous online survey. Results: There is a lack of knowledge about prostate cancer among men in Istria. Most receive information from the media, while a smaller number receive information from physicians. Most have heard that there is a PSA test, but few know that it is a method for early detection. Subjects have different perceptions of digital rectal examination and other screening methods. Some men are afraid of discomfort and pain during the examination, while others do not consider this a problem. Most indicate that they intend to participate in screening in the future and that early detection of prostate cancer is important and a positive attitude towards it influences the decision to participate in the screening program. Conclusion: The lack of knowledge about prostate cancer among men in Croatia is evident. Although most of the respondents do not consider themselves as a risk group, a positive attitude towards early detection affects the participation in prevention programs. Raising awareness and educating men about prostate cancer and available screening methods are key to increasing the number of participants in prevention programs and reducing the incidence of this disease.